Public Satisfaction Index for Public Services at the Air Nipis Sub-District Office, South Bengkulu - Refsi Roziana; Ahmad Soleh; Suswati Nasution (Penerbit Jurnal Indonesia, 2024)
One of the government agencies tasked with providing services to the community is Air Nipis Sub-District Office, South Bengkulu. Air Nipis Sub-District Office, South Bengkulu has the main task of carrying out services to the community and SubDistrict government affairs. The guidelines used to determine the quality of public services provided to the community by Air Nipis Sub-District Office, South Bengkulu refer to the preparation of the Community Satisfaction Index for public service delivery units which is guided by the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. The aim of this research is to determine the Community Satisfaction Index with Public Services at Air Nipis Sub-District Office, South Bengkulu. The analytical method used is the Community Satisfaction Index of public service delivery units based on the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 with 9 indicators in it, namely requirements, procedures, completion time, costs/tariffs, product specifications, types of services, implementing competence, implementing behavior, handling complaints, suggestions and input, facilities and infrastructure. From the analysis of Community Satisfaction Index on the quality of public services Air Nipis SubDistrict Office, South Bengkulu, a value of 76.05 was obtained B in service quality with good criteria because it was in the value interval, namely 62.51-81.25.